The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jfpe.13872
|View full text |Cite
|
Sign up to set email alerts
|

What are the prospects for ultrasound technology in food processing? An update on the main effects on different food matrices, drawbacks, and applications

Abstract: Ultrasound is a promising technology that emerges as a sustainable and low‐cost alternative to conventional food processing. Various advantages are related to this technology, including the improvement of food quality, maintenance of food preservation, reduced processing time, and monitoring of food processes. Despite the extensive knowledge about ultrasonic technologies, it is continually updated, and new applications are constantly discovered. Reported results show that ultrasound can be applied, alone or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 160 publications
(235 reference statements)
0
8
0
Order By: Relevance
“…In addition, it is essential to establish a connection between available information produced in research and the acceptability of the product by consumers. Due to the possibility of working with lower temperatures compared to conventional processes or even other emerging technologies, it has been suggested that losses in sensory aspects could be minimized (Arruda et al., 2021). However, some sensory characteristics of olive oil, such as the pungency and bitterness intensity, were diminished by UAE and, therefore, the obtained oil may be more appreciated by some consumers; however, consumer acceptance did not change when they became aware of more details of the innovative technology (Cavallo et al., 2020).…”
Section: Products From Uae To Food Applicationsmentioning
confidence: 99%
“…In addition, it is essential to establish a connection between available information produced in research and the acceptability of the product by consumers. Due to the possibility of working with lower temperatures compared to conventional processes or even other emerging technologies, it has been suggested that losses in sensory aspects could be minimized (Arruda et al., 2021). However, some sensory characteristics of olive oil, such as the pungency and bitterness intensity, were diminished by UAE and, therefore, the obtained oil may be more appreciated by some consumers; however, consumer acceptance did not change when they became aware of more details of the innovative technology (Cavallo et al., 2020).…”
Section: Products From Uae To Food Applicationsmentioning
confidence: 99%
“…Yu, Su, et al, 2021). Furthermore, the expansion and compression of waves also result in attenuation as energy is lost (Arruda et al, 2021;Khan et al, 2020). Hence, there is an understanding of how the cavitation in diverse food materials, especially liquids or beverages that absorb the energy and scatter US waves, then the physicochemical and rheological characteristics of materials can be altered (Koksel et al, 2016;L.…”
Section: Concepts and Effectsmentioning
confidence: 99%
“…Cavitation is one of the core effects of US on liquid systems wherein these waves in an intense ultrasonic field induce pressure and depression waves at high speed (Gevari et al., 2020; Z. Yu, Su, et al., 2021). Furthermore, the expansion and compression of waves also result in attenuation as energy is lost (Arruda et al., 2021; Khan et al., 2020). Hence, there is an understanding of how the cavitation in diverse food materials, especially liquids or beverages that absorb the energy and scatter US waves, then the physicochemical and rheological characteristics of materials can be altered (Koksel et al., 2016; L. Zhang, Wang, et al., 2020).…”
Section: Fundamentals Of Us Systemsmentioning
confidence: 99%
“…Consumers are more demanding in relation to meat quality, developing new demands, such as increased shelf life and good sensory quality (Lima et al, 2022). The tenderness of the meat is one of the most important elements in the choice of the product, the modification in the intrinsic structure of the meat, for example, increased proteolysis and fragmentation of the myofibrils contribute to the improvement of tenderness (Alarcon-Rojo et al, 2019;Xiong et al, 2020;Arruda et al, 2021;Araújo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%